Exploring Rehabilitation Counseling Supervisors' Role in Promoting Counselor Development of Ethical Fluency. (October 2018) - Landon, Trenton J.; Schultz, Jared C.
Clinical supervision plays an integral role in the professional development of counselors, particularly for developing their awareness of ethical service delivery and decision making. This grounded theory study queried eight rehabilitation counseling supervisors, four from a state rehabilitation agency and four from a nonprofit community rehabilitation organization. The purpose of the study was to determine supervisor perspectives regarding their role in the development of ethical decision making in their supervisees. The emergent construct from the data is termed ethical fluency . Ethical fluency is a cognitive ability representing the interaction between acculturation knowledge, fluid reasoning, and the speed and accuracy with which ethical dilemmas are recognized and processed. Supervisors in this study reported playing a key role in developing ethical fluency in counselors, and the supervisory working alliance was an integral platform from which to approach discussions on ethics. Recommendations for improved practice and future research are provided.